Towards a Model of Learning on Online Social Networking Sites [PowerPoint presentation] - Kamalodeen, Vimala Judy (My University, 2013)
This presentation considers a model to describe how teachers can learn in an online educational social network site (SNS). There are three sections to the presentation: discussions about traditional professional development and teacher learning; exploring educational online social networking sites; and then a look at relevant theories of learning related to online social networking which will lead up to a model of learning on online SNS
Paper presented at the Biennial Conference of The University of the West Indies Schools of Education, 23-25 April, 2013, St. Augustine, Trinidad and Tobago
Keywords: Educational models; Online learning; Teacher education; Teachers; Professional development; Learning theories; Social networking sites